HIF drives lipid deposition and cancer in ccRCC via repression of fatty acid metabolism. Issue 1 (December 2017) - Du, Weinan; Zhang, Luchang; Brett-Morris, Adina; Aguila, Brittany; Kerner, Janos; Hoppel, Charles; Puchowicz, Michelle; Serra, Dolors; Herrero, Laura; Rini, Brian; Campbell, Steven; Welford, Scott
Abstract Clear cell renal cell carcinoma (ccRCC) is histologically defined by its lipid and glycogen-rich cytoplasmic deposits. Alterations in the VHL tumor suppressor stabilizing the hypoxia-inducible factors (HIFs) are the most prevalent molecular features of clear cell tumors. The significance of lipid deposition remains undefined. We describe the mechanism of lipid deposition in ccRCC by identifying the rate-limiting component of mitochondrial fatty acid transport, carnitine palmitoyltransferase 1A (CPT1A ), as a direct HIF target gene.CPT1A is repressed by HIF1 and HIF2, reducing fatty acid transport into the mitochondria, and forcing fatty acids to lipid droplets for storage. Droplet formation occurs independent of lipid source, but only whenCPT1A is repressed. Functionally, repression of CPT1A is critical for tumor formation, as elevated CPT1A expression limits tumor growth. In human tumors, CPT1A expression and activity are decreased versus normal kidney; and poor patient outcome associates with lower expression of CPT1A in tumors in TCGA. Together, our studies identify HIF control of fatty acid metabolism as essential for ccRCC tumorigenesis. Clear cell renal cancers (ccRCC) display elevated intracellular lipid storage. Here the authors show that such lipid accumulation is due to the repression of carnitine palmitoyltransferase 1A (CPT1A) enzyme that impairs fatty acid (FA) transport into the mitochondrion resulting in reduced FA beta oxidation.